BODY IMAGE AND SEXUAL FUNCTIONING IN BREAST CANCER SURVIVORS - Rosman, Lindsey A. (East Carolina University, 2013)
Background: For breast cancer survivors, sexual problems are one of the most common and distressing sequelae of cancer and its treatment. However, sexual problems are often undiagnosed and untreated. One potentially important, but understudied, risk factor for poor sexual adjustment after breast cancer is body image concern. For example, physical changes in appearance as a result of cancer treatment may alter how women perceive themselves and their bodies which may in turn increase risk for sexual problems. Therefore, the current study was designed to evaluate whether body image predicted sexual dysfunction and sexual dissatisfaction following breast cancer. In addition, mediation analyses evaluated body image as a mediator of the relationship between number of cancer-related changes in appearance and sexual dissatisfaction and sexual dysfunction. Mediation analyses also examined body image concerns during sexual activity as a mediator of the relationship between body image concerns and sexual dissatisfaction and dysfunction.   Methods: A sample of 219 U.S. breast cancer survivors was recruited via breast cancer websites, blogs, and social media websites to complete an online self-report survey about body image and sexual functioning after diagnosis and treatment for breast cancer.   Results: Participants' mean age was 47.3 years with an average time since diagnosis of 4.4 years. Women were predominantly European American, married, and diagnosed with Stage I or II breast cancer. On average, women in this sample experienced 6.1 (SD = 2.2) changes in their physical appearance due to cancer treatment, such as hair loss, breast disfigurement and changes to their skin. Sexual problems were common with 69% (n = 72) of sexually active survivors (n = 104) meeting criteria for sexual dysfunction. High levels of body image concerns were also reported. In regression analyses, medical treatment variables, general distress, and body image variables predicted sexual dissatisfaction, whereas only medical treatment variables and general distress predicted sexual dysfunction. Results from mediation analyses indicated that body image mediated the relationship between having a greater number of cancer-related changes in appearance and lower levels of post-treatment sexual dissatisfaction. Two of the body image variables also significantly mediated the relationship between experiencing a greater number of changes in appearance and post-treatment sexual dysfunction. Finally, higher levels of body image concern during sexual activity mediated the relationship between body image and sexual dysfunction as well as sexual dissatisfaction.  Conclusion: Overall, results suggest that body image concerns and sexual problems are prevalent and distressing for a majority of women diagnosed and treated for breast cancer. Many women also experience multiple changes in their physical appearance. In addition, body image concerns may be amplified in a sexual context due to the increased exposure of one's body during sexual activity. Implications for further research, routine assessment, and clinical management of these symptoms are discussed.
Keywords: Clinical psychology; Body image; Breast--Cancer; Sexual adjustment; Breast--Cancer--Patients--Attitudes; Sexual attraction; Body image in women